Recycled Aggregate Concrete and Alternative Binders for Sustainable Building Engineering (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This reprint focuses on the development of sustainable cementitious composites, either by the replacement of natural aggregates with recycled aggregates or by the use of sustainable binding technologies that constitute a viable alternative to Portland cement.